PELATIHAN FOTOGRAFI PRODUK MENGGUNAKAN SMARTPHONE UNTUK MENINGKATKAN VISUAL BRANDING PADA UMKM KERAJINAN TANDUK SAPI DESA PUCANG, MAGELANG - Setya Indah Isnawati; Ari Eko Budiyanto; Ahmad Ali (Sekolah Tinggi Ilmu Ekonomi AMA, 2022)
Product photos with smartphones can be a solution for MSMEs in facing the risk of access to the market. Smartphones are now equipped with cameras and photo editing applications that are very adequate and easy to create visual branding. One of the product photos used in the Community Service (PkM) training this time is product photography. The partner of this PkM is